Effect Of Investment Decision, Capital Structure, Profitability, And Company Size On Company Values - Sumani, Reza Suleman, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study wanted to examine the effect of investment decisions, capital structure, profitability, and company size on the value of the firm, by using samples from the property, real estate, and construction companies listed on the Indonesia stock exchange for the period 2014-2017. Hypothesis testing using the panel data method by using Eviews version 9. The results of the study showed that the investment decision, capital structure, and profitability did not have a significant effect on firm value. In contrast, the size of the company has a significant adverse effect on the value of the firm. From the results of the F test, investment decision, capital structure, profitability, company size in this study simultaneously influence the value of the firm.